Return to the Unity of Body and Mind: Encounter of Asceticism, Therapy and Philosophy in Japan - Masiá Clavel, Juan; Kuwano, Moe (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
The authors have chosen three representative persons, whose thought points the way to return to the basic body-mind unity of the human being through the integration of the power of the unconscious within consciousness: Chih-i (538-597), a Chinese buddhist monk; Yasuo Yuasa (1925-2005), a Japanese philosopher; and Haruchika Noguchi (1911-1976), a Japanese who developed a therapy centered upon the body-mind interrelation. Three of them make a point of focusing spirituality, philosophy or therapy on grasping and using the flow of energy which has been expressed in the chino japanese tradition through the notion of Ki. These oriental traditions, at the crossroads of spirituality, philosophy and therapy are both a contribution and a challenge to the western thought when revisiting the questions about self, identity and personhood in an interdisciplinary and intercultural context.
Keywords: body-mind; oriental philosophy; therapy; Ki